2022
DOI: 10.1200/go.21.00390
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for the Implementation of Geriatric Oncology Principles in Mexico: A Mixed-Methods Study

Abstract: PURPOSE There is limited information regarding the use of the geriatric assessment (GA) for older adults with cancer in developing countries. We aimed to describe geriatric oncology practice among Mexican oncology professionals and to identify barriers and facilitators for the implementation of GA into the routine care of older adults with cancer in Mexico. METHODS We conducted an explanatory sequential mixed-methods study. We administered an online survey to cancer specialists in Mexico about the routine use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…However, only a small percentage of respondents (23.4%) reported using GA and/or geriatric screening tools to assess elderly patients in clinical practice, and surprisingly, 8.1% had never heard of GA. The proportion of physicians who reported performing a GA is comparable to that found in other studies, such as in a survey of cancer providers in the United States (U.S.) (21%) [ 4 ] or a nationwide survey in Mexico (18.9%) [ 20 ]. Studies from European countries, such as Spain, revealed a 31% use of GA in clinical practice [ 21 ], and an older study from the Netherlands showed that 60% of healthcare professionals performed some sort of geriatric evaluation [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, only a small percentage of respondents (23.4%) reported using GA and/or geriatric screening tools to assess elderly patients in clinical practice, and surprisingly, 8.1% had never heard of GA. The proportion of physicians who reported performing a GA is comparable to that found in other studies, such as in a survey of cancer providers in the United States (U.S.) (21%) [ 4 ] or a nationwide survey in Mexico (18.9%) [ 20 ]. Studies from European countries, such as Spain, revealed a 31% use of GA in clinical practice [ 21 ], and an older study from the Netherlands showed that 60% of healthcare professionals performed some sort of geriatric evaluation [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, this is the first survey of its kind in our country, as there were no data reported on this subject so far. Other countries, where knowledge and practices in geriatric oncology were examined by nationwide surveys, revealed a high demand for education, with an overall acceptance that the GA is an evidence-based way to evaluate older adults with cancer, though it is still less frequently used than anticipated [ 4 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review identified 11 relevant publications. 5,6,12,27,[29][30][31][32][33][34] This research has consistently shown that the uptake of GA is generally modest. Thus, in a study of the use and knowledge of GA instruments among US community-based oncologists, Gajra et al 6 found that just 13% of the 349 oncologists surveyed used GA for all of their older patients; 60% of oncologists did not use a formal GA for any of their geriatric patients; and 19% of oncologists reported that they were not aware of any validated GA instruments.…”
Section: Riskmentioning
confidence: 75%
“…For the clinical question concerning the role of GA in older adults with cancer to suggest specific interventions to improve clinical outcomes, the primary outcomes of the nine RCTs included completion of planned chemotherapy (n 5 2) 14,19 ; the proportion of patients with grade 3-5 toxicity (n 5 2) 3,4 ; quality of life (n 5 2) 16,17 ; overall survival (n 5 1) 20 ; a composite criterion of 6-month mortality, functional impairment (fall in the Activities of Daily Living [ADL] score ≥2), and weight loss (≥10%; n 5 1) 18 ; and patient satisfaction with communication about agingrelated concerns (n 5 1). 15 A total of 11 publications were identified by the systematic review and form the evidentiary basis for the Clinical Question 2 guideline recommendations concerning which GA tools should be used to predict outcomes, 5,6,12,[27][28][29][30][31][32][33][34] and help inform the development of the PGA. The identified publications include reports published between 2018 and 2022 of seven clinician surveys, 5,6,12,30,[32][33][34] one systematic literature review, 27 and three narrative literature reviews.…”
Section: Characteristics Of Studies Identified In the Literature Sear...mentioning
confidence: 99%
See 1 more Smart Citation